The Highlander's wild flame - McCollum, Heather (Heather D.) (Brotherhood of Solway Moss, 2024)
"Fearsome Highland warrior Rory MacLeod has sacrificed for his clan. But taken as prisoner in place of his older brother, who’s meant to be laird is more than any man should bear. So when the chance for escape presents itself, Rory risks everything for freedom. But instead of returning to the welcoming warmth of home, Rory steps into a blazing trap...Despite her betrothal to their laird, Lady Sara Macdonald has no love for the MacLeod clan. But when her treacherous father locks the entire MacLeod wedding party into the church and sets fire to it, she cannot stand by and watch the slaughter. Saving them means turning traitor to her clan and becoming an enemy to her own blood...left to the mercy of her greatest enemy. Now her intended husband lies somewhere between life and death, and Sara’s only ally is his younger brother: the fierce MacLeod warrior she’s forbidden to want. And as hunger blazes to life between Rory and Sara unbidden, untamed, and hotter than the fires of Beltane they quickly find themselves caught between honor and a love that will turn blood against blood."--Page 4 of cover